Impact of Unilateral versus Bilateral Breast Reconstruction on Procedure Choices and Outcomes - Taylor, Erin M. (Plast Reconstr Surg, 2019)
BACKGROUND: In choosing between implant-based and autologous breast reconstruction, surgeons and patients must weigh relative risks and benefits. However, differences in outcomes across procedure types may vary between unilateral versus bilateral reconstructions. Procedure-related differences in complications and patient-reported outcomes (PROs) were evaluated for unilateral and bilateral reconstruction. METHODS: Complications and PROs were assessed at two years for patients undergoing autologous (TRAM, DIEP, SIEA) or implant-based (TE, DTI) reconstructions. Overall complications and major complications (requiring re-admission and/or re-operation) were recorded, while PROs were measured with BREAST-Q and PROMIS surveys. Stratified regression models compared outcomes between autologous and implant-based reconstructions, separately for unilateral and bilateral cohorts. RESULTS: Among 2125 patients, 917 underwent unilateral (600 implant, 317 autologous) and 1208 underwent bilateral (994 implant, 214 autologous) reconstructions. Controlling for patient characteristics, complication rates were significantly higher in the autologous versus implant-based group with both unilateral (overall: OR 2.50, p<0.001; major: OR 2.19, p=0.001) and bilateral (overall: OR 2.13, p<0.001; major: OR 1.69, p=0.014) cohorts. In unilateral reconstruction, the autologous group demonstrated significantly better PROs compared to the implant-based group in satisfaction with breast (mean difference=9.85, p<0.001), psychosocial well-being (mean difference=4.84, p=0.006), and sexual well-being (mean difference=11.42, p<0.001). In bilateral reconstruction, the autologous group demonstrated significantly higher PROs only for satisfaction with breast (mean difference=5.13, p=0.001). CONCLUSIONS: Although autologous reconstruction is associated with significantly better PROs compared to implant-based techniques in unilateral reconstruction, procedure choice has far less impact in bilateral reconstruction. Autologous procedures have higher complications rates in both unilateral and bilateral settings.